2002
DOI: 10.3892/ijo.21.1.165
|View full text |Cite
|
Sign up to set email alerts
|

Cell death: Apoptosis versus necrosis (Review)

Abstract: . Cell death and the subsequent post-mortem changes, called necrosis, are integral parts of normal development and maturation cycle. Despite the importance of this process, the mechanisms underlying cell death are still poorly understood. In the recent literature, cell death is said to occur by two alternative, opposite modes: apoptosis, a programmed, managed form of cell death, and necrosis, an unordered and accidental form of cellular dying. The incorrect consequence is the overlapping of: a) the process whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
242
0
9

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(266 citation statements)
references
References 62 publications
(39 reference statements)
10
242
0
9
Order By: Relevance
“…A deficiency of ATP in these steps would prevent downstream processes, including caspase-3 activation. Consistent with results of previous studies showing that low intracellular levels of free ATP might permit apoptotic stimuli to induce necrosis (8,(23)(24)(25)(26), we found that a decrease in the intracellular ATP concentration, induced by inhibition of ATPase, glycolysis, or mitochondrial respiration activities, leads to suppression of caspase-3-like activity (Fig. 4B) and enhancement of cell necrosis (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…A deficiency of ATP in these steps would prevent downstream processes, including caspase-3 activation. Consistent with results of previous studies showing that low intracellular levels of free ATP might permit apoptotic stimuli to induce necrosis (8,(23)(24)(25)(26), we found that a decrease in the intracellular ATP concentration, induced by inhibition of ATPase, glycolysis, or mitochondrial respiration activities, leads to suppression of caspase-3-like activity (Fig. 4B) and enhancement of cell necrosis (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Eradicating tumor cells could be achieved by inducing either apoptosis or necrosis. Apoptosis has advantages over necrosis, in that degradation products are packaged and will be rapidly cleared by phagocytosis, while necrosis involves cell leakage, inflammation, and bystander effects [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In our in vitro study, any possible antiproliferative effect of α-tocopheryl succinate was strongly overlaid by its cytotoxic effects. Increased cytoplasmic granulation, cell swelling, and early plasma membrane leakage strongly pointed to simple primary necrosis [17]. In vivo, simple primary necrosis leads to inflammation of surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…As apoptosis does in general not provoke an inflammatory reponse in vivo [17], death of fibrolasts and inflammatory cells by apoptosis should be an acceptable event in the postoperative period, leading to reduction of scar tissue. However, complications such as bleb leak and infection may occur if the bleb tissue is too extensively devitalized.…”
Section: Discussionmentioning
confidence: 99%